Pengaruh Kemampuan Literasi Digital terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Ekonomi di SMA Negeri 1 Bukit Sundi - Wina Roza Fahira Roza; Desi Armi Eka Putri; Fajri Basyirun (CV.RIZANIA MEDIA PRATAMA, 2024)
This research was motivated by the low learning outcomes of class This research aims to find out how much influence Digital Literacy Skills have on the Learning Outcomes of Class X Students in Economics Subjects at SMA Negeri 1 Bukit Sundi. This type of research is quantitative research. The population in the study were all class X students at SMA Negeri 1 Bukit Sundi in the 2023/2024 academic year, namely 162 people. Sampling was carried out using a simple random sampling technique of 115 people. The analysis technique used is a simple linear regression analysis technique.The results of this research show that digital literacy skills on learning outcomes show a value (Sig) of 0.00<0.05 and a value of tcount>ttable (17.858>1.661) meaning that Ha is accepted and H0 is rejected. Based on the results, it can be concluded that there is a positive and significant influence of digital literacy skills on the learning outcomes of class X students in economics subjects at SMA Negeri 1 Bukit Sundi. The magnitude of the influence of digital literacy skills on learning outcomes is 73.8%.